600MPa grade high-strength earthquake-resistant steel bar and production method thereof
By using low silicon niobium vanadium nitrogen combined with a small amount of chromium/boron/copper composition in high-strength seismic steel bars and a control rolling process, the problem of not being able to achieve both strength and surface quality of the steel bars is solved, and the improvement of high strength, plasticity and seismic performance and the guarantee of surface quality are achieved.
Patent Information
- Application Number
- CN202510139178.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The existing high-strength seismic steel bars have low strength levels, and the yield strength is below 500MPa. The high-temperature rolling process can easily lead to bubbles on the surface of the steel bars, affecting density and roughness, and thus affecting the interface combination between the steel bars and concrete.
Low silicon niobium vanadium nitrogen combined with a small amount of chromium/boron/copper composition design, combined with rolling process parameters, including heating, descaling, rolling and cooling processes, controlling the final rolling temperature and cooling speed, and eliminating bubbles on the surface of the steel bar.
The high strength, plasticity and seismic resistance of steel bars are achieved, while ensuring the surface quality of steel bars and enhancing the interface bonding force with concrete.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of steel smelting, and in particular to a 600MPa grade high-strength earthquake-resistant steel bar and a production method thereof. Background Art
[0002] The use of high-strength earthquake-resistant steel bars can reduce the amount of steel bars used, improve the safety of building structures, shorten the construction period, and have significant economic, social and ecological benefits. It has become an important building material and is suitable for large-span, heavy-load, and super-high-rise building structures. The existing high-strength earthquake-resistant steel bar products have low strength levels and yield strengths below 500MPa, which cannot meet the use requirements. In order to improve the strength of steel bars, micro-alloying component systems such as niobium, vanadium, and titanium are used. Through the regulation of rolling process parameters, such as high-temperature heating and high upper cooling bed temperature, to ensure the solid solution of alloy elements, regulate grain size and organizational type, the synergistic improvement of steel bar strength, plasticity, and earthquake resistance is achieved. However, the high-temperature rolling process easily causes bubbles to form on the surface of the steel bar, affecting the density and roughness, and thus affecting the interface bonding between the steel bar and the concrete. Summary of the invention
[0003] The purpose of the present application is to provide a steel bar and a production method thereof, which adopts a design of low silicon, niobium, vanadium and nitrogen with a small amount of chromium / boron / copper components, combined with the regulation of rolling process parameters, to solve the problem in the prior art that both the strength and surface quality of the steel bar cannot be achieved.
[0004] In order to achieve one of the above-mentioned invention purposes, an embodiment of the present application provides a method for producing steel bars, wherein the steel bars contain the following components by weight percentage: C: 0.20-0.30%, Si: 0.10-0.30%, Mn: 1.00-2.00%, V: 0.1-0.2%, Nb: 0.01-0.03%, N: 0.015-0.025%, at least one of Cr, Cu, and B, and 1≤([Cr]+[B]+[Cu]) / [Si]≤2, and Cr, Cu, and B in the steel bars by weight percentage also satisfy: Cr: 0.1-0.3%, B: 0.001-0.010%, Cu: 0.1-0.3%, and the rest are iron and impurity elements;
[0005] The method for producing steel bars comprises heating, descaling, rolling and cooling a steel billet having the chemical composition as described above to obtain steel bars, wherein:
[0006] During the heating process, the temperature of the steel billet in the soaking section of the heating furnace is 1200~1250℃;
[0007] In the rolling process, the steel billet is placed in a rolling mill and rolled into steel bars, and the final rolling temperature is controlled to be greater than 1100°C;
[0008] In the cooling process, after rolling is completed, the steel bars are cooled by water cooling and then sent to a cooling bed to cool naturally to room temperature in the air. The cooling rate during water cooling is controlled to be 2~5℃ / s, the temperature of the cooling bed on the steel bars is 1040~1080℃, and the cooling rate during natural cooling is <1℃ / s.
[0009] In one embodiment of the present application, in the descaling process, the heated steel billet is descaled using high-pressure water with a water pressure of 1-2 MPa.
[0010] In one embodiment of the present application, the heating process further includes smelting, LF refining and continuous casting steps performed in sequence, wherein:
[0011] In the smelting process, alloy and slag are added in the order of silicon-manganese alloy, lime and fluorite. The amount of silicon-manganese alloy added is 10~30kg / t, and the manganese content in the silicon-manganese alloy is 65~70%, the silicon content is 17~20%, and the rest is iron and other impurity elements.
[0012] In one embodiment of the present application, in the smelting process, the steel tapping temperature is controlled at 1595~1635°C, and the argon blowing control valve at the bottom of the ladle is opened before steel tapping, and argon is blown throughout the steel tapping process. The argon pressure is controlled at 0.4~0.5MPa in the first 1 / 3 section before steel tapping, and the argon pressure is controlled at 0.3~0.4MPa in the last 2 / 3 section after steel tapping.
[0013] In one embodiment of the present application, in the LF refining process, ferrovanadium and ferroniobium are added to the ladle at the station respectively, and high carbon ferrochromium alloy, copper block and ferroboron alloy are selectively added according to the above-mentioned components of the steel bar, wherein the amount of ferrovanadium alloy added is 1.5~3kg / t, the vanadium content in the ferrovanadium alloy is 45~50%, and the rest is iron and other impurity elements; the amount of ferroniobium alloy added is 0.3~0.6kg / t, the niobium content in the ferroniobium alloy is 40~45%, and the rest is iron and other impurity elements; the amount of high carbon ferrochromium alloy added is 1~3kg / t, the chromium content in the high carbon ferrochromium alloy is 53~57%, the carbon content is 8~12%, and the rest is iron and other impurity elements; the amount of copper block added is 1~3kg / t; the amount of ferroboron alloy added is 0.15~1.5kg / t, the boron content in the ferroboron alloy is 15~20%, and the rest is iron and other impurity elements.
[0014] In one embodiment of the present application, in the LF refining process, nitrogen blowing begins after the ladle is powered on. During nitrogen blowing, the nitrogen flow rate is controlled to be 650~800L / min, the nitrogen pressure is controlled to be 0.1~0.3MPa, and the nitrogen blowing time is 10~15min; argon is not blown during nitrogen blowing. After the nitrogen blowing is completed, the argon control valve is opened to carry out argon blowing and soft stirring. The argon blowing time is ≥5min, and the LF refining steelmaking temperature is 1545~1565℃.
[0015] In one embodiment of the present application, in the continuous casting process, the casting speed is controlled to be 2.5~2.9m / min, and the water flow rate of the crystallizer is 1900~2000L / min.
[0016] An embodiment of the present application also provides a steel bar prepared according to the above-mentioned steel bar production method, wherein the steel bar comprises the following components by weight percentage: C: 0.20~0.30%, Si: 0.10~0.30%, Mn: 1.00~2.00%, V: 0.1~0.2%, Nb: 0.01~0.03%, N: 0.015~0.025%, at least one of Cr, Cu, and B, and 1≤([Cr]+[B]+[Cu]) / [Si]≤2, and the Cr, Cu, and B in the steel bar also meet the following requirements by weight percentage: Cr: 0.1~0.3%, B: 0.001~0.010%, Cu: 0.1~0.3%, and the rest are iron and impurity elements.
[0017] In one embodiment of the present application, the steel bar comprises the following components by weight percentage: C: 0.24~0.28%, Si: 0.15~0.25%, Mn: 1.40~1.60%, V: 0.12~0.14%, Nb: 0.015~0.025%, N: 0.015~0.020%, at least one of Cr, Cu, and B, and 1≤([Cr]+[B]+[Cu]) / [Si]≤2, and the Cr, Cu, and B in the steel bar also satisfy the following by weight percentage: Cr: 0.1~0.3%, B: 0.001~0.010%, Cu: 0.1~0.3%, and the rest are iron and impurity elements.
[0018] In one embodiment of the present application, the structure of the steel bar includes ferrite, pearlite and bainite, wherein the sum of the volume proportion of ferrite and the volume proportion of pearlite is ≥93%, and the volume proportion of pearlite is 50~65%, the average size of pearlite clusters is 8~10μm, and the average size of ferrite grains is 4~6μm.
[0019] In one embodiment of the present application, the yield strength is ≥620MPa, the tensile strength is ≥790MPa, the elongation after fracture is ≥20%, the total elongation at maximum force is ≥13%, and the strength-to-yield ratio is ≥1.27.
[0020] One or more technical solutions provided by this application have at least the following technical effects or advantages:
[0021] The production method of the steel bars provided in the present application adopts a design of low silicon niobium vanadium nitrogen combined with a small amount of chromium / boron / copper components, and combines the rolling process parameter regulation to obtain an ideal complex phase structure of ferrite + pearlite + a small amount of bainite, giving full play to the precipitation strengthening and phase transformation strengthening effects of the alloy elements, while regulating the composition and structure of the surface iron oxide scale. Under the conditions of existing production line equipment, bubbles on the surface of the steel bars are eliminated, ensuring the strength, plasticity, seismic resistance and surface quality of the steel bars. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The embodiment of the present application provides a method for producing steel bars, wherein the steel bars contain the following components by weight percentage: C: 0.20~0.30%, Si: 0.10~0.30%, Mn: 1.00~2.00%, V: 0.1~0.2%, Nb: 0.01~0.03%, N: 0.015~0.025%, at least one of Cr, Cu, and B, and 1≤([Cr]+[B]+[Cu]) / [Si]≤2, and the Cr, Cu, and B in the steel bars by weight percentage also satisfy the following: Cr: 0.1~0.3%, B: 0.001~0.010%, Cu: 0.1~0.3%, and the rest are iron and impurity elements; wherein [Cr], [B], [Cu], and [Si] are the weight percentages of the corresponding elements, respectively.
[0024] The method for producing steel bars comprises heating, descaling, rolling and cooling a steel billet having the chemical composition as described above to obtain steel bars, wherein:
[0025] During the heating process, the temperature of the steel billet in the soaking section of the heating furnace is 1200~1250℃;
[0026] In the rolling process, the steel billet is placed in a rolling mill and rolled into steel bars, and the final rolling temperature is controlled to be greater than 1100°C;
[0027] In the cooling process, after rolling is completed, the steel bars are cooled by water cooling and then sent to a cooling bed to cool naturally to room temperature in the air. The cooling rate during water cooling is controlled to be 2~5℃ / s, the temperature of the cooling bed on the steel bars is 1040~1080℃, and the cooling rate during natural cooling is <1℃ / s.
[0028] This application adopts a low silicon niobium vanadium nitrogen and a small amount of chromium / boron / copper composition system. While ensuring deoxidation, solid solution strengthening and organizational regulation, the silicon element can inhibit the formation of excessive silicate oxides on the surface of the steel billet when it is heated at high temperature; ensure that the high-temperature heated steel billet obtains a clean surface after dephosphorization, and realizes the regulation of the composition and structure of the iron oxide scale on the surface of the steel bar. A higher temperature is used in the heating process to increase the solid solution carbon content, improve the stability of austenite, and delay the phase transformation of pearlite and bainite; by adding a certain amount of hardenability elements (chromium, boron, copper), combined with the rolling process, the formation of hard phase structure can be promoted; after rolling, a weak water penetration process (cooling rate of 2~5℃ / s) is used to ensure the strengthening effect of hardenability elements such as copper, chromium, and boron. At the same time, a faster cooling rate passes through the formation temperature range of silicate oxides, which is conducive to eliminating bubbles on the surface of the steel bar and realizing the regulation of the composition and structure of the iron oxide scale on the surface of the steel bar.
[0029] The effects of each chemical component have the following characteristics:
[0030] Carbon (C): A strengthening element that can significantly improve the strength of steel bars. However, too high a carbon content is detrimental to the plasticity, toughness and welding properties of steel. Taking all factors into consideration, the carbon content is controlled at 0.2-0.3%; when the carbon content is 0.24-0.28%, the effect is better.
[0031] Silicon (Si): A strengthening element that can simultaneously improve the yield strength and tensile strength of steel bars through solid solution strengthening. However, if the silicon content is too high, silicate oxides are easily generated at high temperatures, which cover the surface of the steel and are difficult to remove, affecting the surface quality of the steel bars. Taking all factors into consideration, the silicon content is controlled to be 0.10~0.30%; when the silicon content is 0.15~0.25%, the effect is better.
[0032] Manganese (Mn): A solid solution strengthening element that can significantly improve the strength and toughness of steel; however, if the manganese content is too high, it will increase the hardenability and easily form MnS inclusions, reducing the plasticity of the steel. Taking all factors into consideration, the manganese content is controlled at 1.0~2.0%; when the Mn content is 1.4~1.6%, the effect is better.
[0033] Vanadium (V): Vanadium is a strong carbonitride-forming element. Through the precipitation of carbonitrides, it can significantly improve the strength and toughness of steel. However, the strengthening effect of vanadium is affected by the nitrogen content. When the vanadium content is too high, the effect of further improving the strength is not obvious. Taking all factors into consideration, the vanadium content is controlled at 0.1~0.2%; when the vanadium content is controlled at 0.12~0.14%, the effect is better.
[0034] Niobium (Nb): Improves the strength and toughness of steel through precipitation strengthening and fine grain strengthening; Niobium-containing steel can promote the formation of hard phase structure through rolling process control, which is beneficial to adjust the strength, plasticity and seismic resistance of steel bars; but if the niobium content is too high, the billet is prone to cracks during continuous casting. Taking all factors into consideration, the niobium content is controlled to 0.01~0.03%; when the niobium content is 0.015~0.025%, the effect is better.
[0035] Nitrogen (N): It is a solid solution strengthening element and combines with niobium and vanadium to form carbonitrides to improve strength. However, if the content is too high, it will be detrimental to plasticity. If the content is too low, the smelting difficulty will increase and the strengthening element will not play its role fully. Taking all factors into consideration, the nitrogen content is controlled at 0.015~0.025%; when the nitrogen content is 0.015~0.020%, the effect is better.
[0036] Chromium (Cr), boron (B), copper (Cu): hardenability elements, combined with rolling process control, can promote the formation of hard phase structure and improve strength; but too high content can easily lead to excessive hard phase structure or abnormal structure. Comprehensive consideration, 1≤([Cr]+[B]+[Cu]) / [Si]≤2, and the chromium content is 0.1~0.3%, the boron content is 0.001~0.010%, and the copper content is 0.1~0.3%.
[0037] In one embodiment of the present application, in the descaling process, the heated steel billet is descaled using high-pressure water with a water pressure of 1-2 MPa. Iron oxide scale will form on the surface of the steel billet after heating. The high-pressure water is used to remove the iron oxide scale on the surface of the steel billet, thereby improving the surface quality of the steel billet, so that the steel bars that are subsequently rolled also have good surface quality.
[0038] In one embodiment of the present application, the heating process further includes smelting, LF refining and continuous casting processes performed in sequence, wherein:
[0039] In the smelting process, alloy and slag are added in the order of silicon-manganese alloy, lime and fluorite. The amount of silicon-manganese alloy added is 10~30kg / t, and the manganese content in the silicon-manganese alloy is 65~70%, the silicon content is 17~20%, and the rest is iron and other impurity elements. No ferrosilicon alloy is added during the smelting stage, and the silicon content is brought in by the silicon-manganese alloy, so the alloy cost is low. The silicon in the silicon-manganese alloy is not only used for deoxidation, but also provides silicon elements in the steel bars.
[0040] Furthermore, in the smelting process, the tapping temperature is controlled at 1595~1635℃, and the argon blowing control valve at the bottom of the ladle is opened before tapping. Argon is blown throughout the tapping process, and the argon pressure is controlled at 0.4~0.5MPa in the first 1 / 3 section before tapping, and 0.3~0.4MPa in the second 2 / 3 section after tapping. The argon pressure is relatively high in the early stage of blowing, providing strong soft stirring to homogenize the molten steel, and is relatively gentle in the later stage, which is conducive to stable tapping.
[0041] In one embodiment of the present application, in the LF refining process, ferrovanadium and ferroniobium are added to the ladle at the station respectively, and high carbon ferrochromium, copper blocks and ferroboron are selectively added according to the above-mentioned components of the steel bar, wherein the amount of ferrovanadium added is 1.5~3kg / t, the vanadium content in the ferrovanadium is 45~50%, and the rest is iron and other impurity elements; the amount of ferroniobium added is 0.3~0.6kg / t, the niobium content in the ferroniobium is 40~45%, and the rest is iron and other impurity elements; the amount of high carbon ferrochromium added is 1~3kg / t, the chromium content in the high carbon ferrochromium is 53~57%, the carbon content is 8~12%, and the rest is iron and other impurity elements; the amount of copper blocks added is 1~3kg / t; the amount of ferroboron added is 0.15~1.5kg / t, the boron content in the ferroboron is 15~20%, and the rest is iron and other impurity elements.
[0042] Furthermore, in the LF refining process, nitrogen blowing begins after the ladle is powered on. During nitrogen blowing, the nitrogen flow rate is controlled to be 650~800L / min, the nitrogen pressure is controlled to be 0.1~0.3MPa, and the blowing time is 10~15min. During nitrogen blowing, the argon gas is turned off, and after the nitrogen blowing is completed, the argon control valve is opened to perform argon blowing soft stirring. The argon blowing time is ≥5min, and the LF refining tapping temperature is 1545~1565℃. Blowing nitrogen into the molten steel can, on the one hand, play a soft stirring role, making vanadium, niobium, chromium / copper / boron more uniform in the molten steel, and on the other hand, can add nitrogen to the molten steel. Compared with the existing nitrogen addition process, the nitrogen addition process by nitrogen blowing is simple and economical.
[0043] In one embodiment of the present application, in the continuous casting process, the casting speed is controlled to be 2.5~2.9m / min, and the water flow rate of the crystallizer is 1900~2000L / min. During continuous casting, a large ladle long water nozzle and sealing pad, an immersion water nozzle, and a tundish covering agent are used for full protection casting, and argon is blown at the long water nozzle. In addition, the crystallizer electromagnetic stirring current is 350A, the frequency is 3~5Hz, and the secondary cooling water volume is automatically distributed according to the parameters (L / m) in the following table:
[0044]
[0045] The embodiment of the present application also provides a steel bar prepared according to the above-mentioned steel bar production method, the steel bar comprises the following components by weight percentage: C: 0.20~0.30%, Si: 0.10~0.30%, Mn: 1.00~2.00%, V: 0.1~0.2%, Nb: 0.01~0.03%, N: 0.015~0.025%, at least one of Cr, Cu, and B, and 1≤([Cr]+[B]+[Cu]) / [Si]≤2, and the Cr, Cu, and B in the steel bar also meet the following requirements by weight percentage: Cr: 0.1~0.3%, B: 0.001~0.010%, Cu: 0.1~0.3%, and the rest are iron and impurity elements.
[0046] Preferably, the steel bar contains the following components by weight percentage: C: 0.24~0.28%, Si: 0.15~0.25%, Mn: 1.40~1.60%, V: 0.12~0.14%, Nb: 0.015~0.025%, N: 0.015~0.020%, at least one of Cr, Cu, and B, and 1≤([Cr]+[B]+[Cu]) / [Si]≤2. The Cr, Cu, and B in the steel bar also satisfy the following by weight percentage: Cr: 0.1~0.3%, B: 0.001~0.010%, Cu: 0.1~0.3%, and the rest are iron and impurity elements.
[0047] In one embodiment of the present application, the structure of the steel bar includes ferrite, pearlite and bainite, wherein the sum of the volume proportions of ferrite and pearlite is ≥93%, and the volume proportion of pearlite is 50~65%, the average size of pearlite clusters is 8~10μm, and the average size of ferrite grains is 4~6μm.
[0048] In one embodiment of the present application, the yield strength of the steel bar is ≥620 MPa, the tensile strength is ≥790 MPa, the elongation after fracture is ≥20%, the total elongation at maximum force is ≥13%, and the strength-yield ratio is ≥1.27.
[0049] The surface of the high-strength earthquake-resistant steel bar in the present application is free of bubbles. An electron probe is used to perform a surface scan of the edge area (iron oxide layer) of the steel bar cross section, and no enrichment of silicon is found.
[0050] The technical solution of the present application is further described below in conjunction with some specific embodiments.
[0051] The present application provides the following steel bars of Examples 1 to 6 and Comparative Examples 1 to 5, which are prepared through converter, LF refining, continuous casting, heating, rolling and cooling processes, wherein Table 1 shows the weight percentages of chemical components of the steel bars of Examples 1 to 6 and Comparative Examples 1 to 5, Table 2 shows the process parameters of the smelting process of Examples 1 to 6 and Comparative Examples 1 to 5, Table 3 shows the process parameters of the LF refining process of Examples 1 to 6 and Comparative Examples 1 to 5, Table 4 shows the process parameters of the continuous casting process of Examples 1 to 6 and Comparative Examples 1 to 5, and Table 5 shows the process parameters of the heating, rolling and cooling processes of Examples 1 to 6 and Comparative Examples 1 to 5.
[0052] The structures and properties of Examples 1 to 6 and Comparative Examples 1 to 5 obtained by referring to the standards GB / T13298 "Metallic Microstructure Test Methods", GB / T28900 "Test Methods for Steel for Reinforced Concrete" and GB / T228.1 "Metallic Material Tensile Test Part 1 Room Temperature Test Methods" are shown in Table 6.
[0053] Table 1 Chemical composition of examples and comparative examples (%)
[0054]
[0055] Table 2 Production process parameters (smelting process) of the embodiments and comparative examples
[0056]
[0057] Table 3 Production process parameters of embodiments and comparative examples (LF refining)
[0058]
[0059] Table 4 Production process parameters (continuous casting) of the embodiments and comparative examples
[0060]
[0061] Table 5 Production process parameters (heating, rolling, cooling) of the embodiments and comparative examples
[0062]
[0063] Table 6 Organization and performance of examples and comparative examples
[0064]
[0065] Note: In the structure column of Table 6, F stands for ferrite, P stands for pearlite, and B stands for bainite.
[0066] It can be seen from Tables 1 to 6 that the yield strength of the high-strength earthquake-resistant steel bars provided in the implementation mode of the present application is ≥620 MPa, the tensile strength is ≥790 MPa, the elongation after fracture is ≥20%, the total elongation at maximum force is ≥13%, the strength-to-yield ratio is >1.27, and there are no bubbles on the surface; the comprehensive performance is significantly better than that of comparative examples 1 to 5.
[0067] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0068] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present application. They are not intended to limit the scope of protection of the present application. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present application should be included in the scope of protection of the present application.
Claims
1. A method for producing steel bars, characterized in that: The steel bar contains the following components by weight percentage: C: 0.20-0.30%, Si: 0.10-0.30%, Mn: 1.00-2.00%, V: 0.1-0.2%, Nb: 0.01-0.03%, N: 0.015-0.025%, at least one of Cr, Cu and B, and 1≤([Cr]+[B]+[Cu]) / [Si]≤2, and the Cr, Cu and B in the steel bar by weight percentage also meet the following requirements: Cr: 0.1-0.3%, B: 0.001-0.010%, Cu: 0.1-0.3%, and the rest are iron and impurity elements; The production method of steel bars comprises heating, descaling, rolling and cooling steel billets having the chemical composition as described above to obtain steel bars, wherein: During the heating process, the temperature of the steel billet in the soaking section of the heating furnace is 1200~1250℃; In the rolling process, the steel billet is placed in a rolling mill and rolled into steel bars, and the final rolling temperature is controlled to be greater than 1100°C; In the cooling process, after rolling is completed, the steel bars are cooled by water cooling and then sent to a cooling bed to cool naturally to room temperature in the air. The cooling rate during water cooling is controlled to be 2~5℃ / s, the temperature of the cooling bed on the steel bars is 1040~1080℃, and the cooling rate during natural cooling is <1℃ / s.
2. The method for producing a steel bar according to claim 1, characterized in that: In the descaling process, the heated steel billet is descaled using high-pressure water at a water pressure of 1~2MPa.
3. The method for producing a steel bar according to claim 1, characterized in that: The heating process also includes smelting, LF refining and continuous casting processes in sequence, wherein: In the smelting process, alloy and slag are added in the order of silicon-manganese alloy, lime and fluorite. The amount of silicon-manganese alloy added is 10~30kg / t, and the manganese content in the silicon-manganese alloy is 65~70%, the silicon content is 17~20%, and the rest is iron and other impurity elements.
4. The method for producing a steel bar according to claim 3, characterized in that: During the smelting process, the steel tapping temperature is controlled at 1595~1635℃, and the argon blowing control valve at the bottom of the ladle is opened before tapping. Argon is blown throughout the entire steel tapping process. The argon pressure is controlled at 0.4~0.5MPa in the first 1 / 3 section before tapping, and at 0.3~0.4MPa in the last 2 / 3 section after tapping.
5. The method for producing a steel bar according to claim 3, characterized in that: In the LF refining process, ferrovanadium and ferroniobium are added to the ladle at the station respectively, and high carbon ferrochromium, copper blocks and ferroboron are selectively added according to the above-mentioned components of the steel bars, wherein the amount of ferrovanadium added is 1.5~3kg / t, the vanadium content in the ferrovanadium alloy is 45~50%, and the rest is iron and other impurity elements; the amount of ferroniobium added is 0.3~0.6kg / t, the niobium content in the ferroniobium alloy is 40~45%, and the rest is iron and other impurity elements; the amount of high carbon ferrochromium added is 1~3kg / t, the chromium content in the high carbon ferrochromium alloy is 53~57%, the carbon content is 8~12%, and the rest is iron and other impurity elements; the amount of copper blocks added is 1~3kg / t; the amount of ferroboron added is 0.15~1.5kg / t, the boron content in the ferroboron alloy is 15~20%, and the rest is iron and other impurity elements.
6. The method for producing a steel bar according to claim 5, characterized in that: In the LF refining process, nitrogen blowing begins after the ladle is powered on. During nitrogen blowing, the nitrogen flow rate is controlled to 650~800L / min, the nitrogen pressure is controlled to 0.1~0.3MPa, and the nitrogen blowing time is 10~15min. Argon is not blown during nitrogen blowing. After the nitrogen blowing is completed, the argon control valve is opened to carry out argon blowing and soft stirring. The argon blowing time is ≥5min, and the LF refining steelmaking temperature is 1545~1565℃.
7. The method for producing a steel bar according to claim 3, characterized in that: During the continuous casting process, the casting speed is controlled at 2.5~2.9m / min and the water flow rate of the crystallizer is 1900~2000L / min.
8. A steel bar prepared according to the method for producing a steel bar as claimed in claim 1, wherein the steel bar comprises the following components by weight percentage: C: 0.20-0.30%, Si: 0.10-0.30%, Mn: 1.00-2.00%, V: 0.1-0.2%, Nb: 0.01-0.03%, N: 0.015-0.025%, at least one of Cr, Cu and B, and 1≤([Cr]+[B]+[Cu]) / [Si]≤2, and the Cr, Cu and B in the steel bar by weight percentage also satisfy: Cr: 0.1-0.3%, B: 0.001-0.010%, Cu: 0.1-0.3%, and the rest are iron and impurity elements.
9. The steel bar according to claim 8, characterized in that The steel bar contains the following components by weight percentage: C: 0.24~0.28%, Si: 0.15~0.25%, Mn: 1.40~1.60%, V: 0.12~0.14%, Nb: 0.015~0.025%, N: 0.015~0.020%, at least one of Cr, Cu and B, and 1≤([Cr]+[B]+[Cu]) / [Si]≤2. The Cr, Cu and B in the steel bar also satisfy the following by weight percentage: Cr: 0.1~0.3%, B: 0.001~0.010%, Cu: 0.1~0.3%, and the rest are iron and impurity elements.
10. The steel bar according to claim 8, characterized in that The microstructure of the steel bar includes ferrite, pearlite and bainite, among which the sum of the volume proportions of ferrite and pearlite is ≥93%, and the volume proportion of pearlite is 50~65%, the average size of pearlite clusters is 8~10μm, and the average size of ferrite grains is 4~6μm.
11. The steel bar according to claim 8, characterized in that Its yield strength is ≥620MPa, tensile strength is ≥790MPa, elongation after fracture is ≥20%, total elongation at maximum force is ≥13%, and strength-to-yield ratio is ≥1.27.
Citation Information
Patent Citations
Method for producing niobium-contained HRB400 grade reinforcing steel
CN101007316A
Yield strength 700MPa grade atmospheric corrosion resistant steel and method for manufacturing same
CN101135029A